2005
DOI: 10.1158/0008-5472.can-04-3169
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Transfer of Tumor-Reactive Transforming Growth Factor-β–Insensitive CD8+ T Cells: Eradication of Autologous Mouse Prostate Cancer

Abstract: Transforming growth factor (TGF)-B is a potent immunosuppressant. Overproduction of TGF-B by tumor cells may lead to tumor evasion from the host immune surveillance and tumor progression. The present study was conducted to develop a treatment strategy through adoptive transfer of tumor-reactive TGF-B-insensitive CD8 + + T cells. The mouse TRAMP-C2 prostate cancer cells produced large amounts of TGF-B1 and were used as an experimental model. C57BL/6 mice were primed with irradiated TRAMP-C2 cells. CD8 + + T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 30 publications
3
97
0
Order By: Relevance
“…Reasons for the lack of in vitro CTL activity are unclear but could include: (a) no TRAMP-C2 -specific CTLs were generated in this model system. A recent study reported that TRAMP-C2 cells secrete large amounts of the potent immunosuppressant transforming growth factor-h, which could prevent CD8 + cells from infiltrating into metastatic lung tumors (36). Based on this report, we did in vitro stimulation of splenocytes with TRAMP-C2 cells in the presence of antitransforming growth factor-h antibodies; however, the CTL assay was again unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for the lack of in vitro CTL activity are unclear but could include: (a) no TRAMP-C2 -specific CTLs were generated in this model system. A recent study reported that TRAMP-C2 cells secrete large amounts of the potent immunosuppressant transforming growth factor-h, which could prevent CD8 + cells from infiltrating into metastatic lung tumors (36). Based on this report, we did in vitro stimulation of splenocytes with TRAMP-C2 cells in the presence of antitransforming growth factor-h antibodies; however, the CTL assay was again unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tumors have been shown to escape the anti-tumor immune responses by generating an immunosuppressed tumor microenvironment. Tumors often produce soluble immunosuppressive factors, such as TGFβ [13,68,69], VEGF [69,70], IL-10 [69,71], iNOS [72,73], PGE 2 [74,75], and gangliosides [76,77], that act on neutrophils and other tumor infiltrating immune cells. Often, progressive immunosuppression is observed at advanced tumor stages, which is partially mediated by tumor-infiltrating immunosuppressive immune cells such as regulatory T (Treg) cells, Th17 cells, regulatory dendritic cells, TAMs, TANs and MDSCs.…”
Section: Immunosuppression In the Tumor Microenvironmentmentioning
confidence: 99%
“…These ex vivo expanded TGFβ-insensitive CD8 + T cells infiltrated the tumor and mediated apoptosis in tumor cells [68]. Fridlender et al [13] showed that inhibition of TGFβ signaling using the small molecule inhibitor SM16 conferred anti-tumorigenic activity to neutrophils.…”
Section: Tgfβmentioning
confidence: 99%
“…While active TGF-β does not inhibit lysis by CTLs, it can inhibit maturation of T cells to that effector state [79]. This explains, at least in part, how CD8 + T cells resistant to TGF-β1 can mediate tumor rejection [80].…”
Section: The Immunosuppressive Environment Inside Tumorsmentioning
confidence: 99%